The awareness of cleanliness among students of UiTM Kota Bharu / Faten Ainon Najwa Arba … [et al.] - Arba, Faten Ainon Najwa; Zakaria, Najah Syamimi; Wan Kamal, Wan Nurul Anis; Hamzah, Nor Hazreeni; Ibrahim, Nur Safwati; Ibrahim, Nurul Bariyah (Akademi Pengajian Bahasa, 2021)
Cleanliness is a state of being clean. Today’s pandemic of Coronavirus 2019, Covid- 19 is greatly associated with cleanliness. This study was done to identify the awareness of cleanliness among students of UiTM Kota Bharu based on gender, academic achievement, peer, and environmental influence. A cross-sectional correlational design was used in this study with a sample of 301 respondents. The aims of this study were to identify the mean different between gender and academic achievement on the awareness of cleanliness. Besides, this study also aimed to identify the influential factor towards the awareness of cleanliness. Independent t-test, one-way ANOVA and multiple linear regression was used in order to answer the objectives. It was found that both gender and academic achievement had no significance difference on the awareness of cleanliness. It was also revealed that, peer influence and environmental influence significantly influenced the awareness of cleanliness among students.